Exponential increase of signal crayfish in running waters in Sweden – due to illegal introductions? - Bohman P.; Degerman E.; Edsman L.; Sers B. (Knowledge and Management of Aquatic Ecosystems, 2011)
Sweden has only one indigenous species of crayfish, the noble crayfish (Astacus astacus, Fabricius). There has been a steady decline of noble crayfish populations in Sweden since 1907, mainly due to the crayfish plague. To substitute the noble crayfish fishery lost, the Swedish government launched a large-scale introduction of the signal crayfish (Pacifastacus leniusculus Dana). Today, the signal crayfish is regarded as a chronic carrier of the crayfish plague, and an expansion of the species may seriously threaten the noble crayfish. This paper examines the decrease of noble crayfish populations, and the concurrent expansion of signal crayfish in running waters. Data from the Swedish Electrofishing RegiSter (SERS) was used. We found that in 1980–1984 the noble crayfish occurred in 4.5% of the studied river sections. In 2008–2009 the occurrences had decreased to 1.9%. In contrast, the signal crayfish had increased in occurrence, from 0.2% (1980–1984) to 11.8% in (2008–2009). We studied the number of stocking permits for signal crayfish introductions, and the available signal crayfish population from the open fishery in Lake Vättern, as possible causes of this expansion. A negative correlation between stocking permits and increased occurrence in streams, and a positive correlation between the availability of crayfish in Lake Vättern and the occurrence in streams was found. This suggests that the expansion of signal crayfish may be due to illegal introductions, further endangering the endemic noble crayfish.